2021
DOI: 10.1177/03000605211059929
|View full text |Cite
|
Sign up to set email alerts
|

Embolectomy of acute embolic stroke associated with ipsilateral carotid web: a case report and literature review

Abstract: A carotid web is a thin intraluminal protrusion located in the posterolateral wall of the carotid bulb, which might be a risk factor for cryptogenic stroke. The mechanism of ischemic stroke caused by carotid web is still unclear, but it might be related to hemodynamic changes distal to the web, resulting in flow forces and remote embolization of fibrin-based clots. The diagnosis of a carotid web mainly depends on carotid artery imaging examinations. The main therapeutic strategies include medical treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“… 5 ) A cohort study also demonstrated that among seven (29%) patients with symptomatic CaWs exhibiting a recurrent ischemic stroke, three were already taking antiplatelet monotherapy and two were using dual antiplatelet therapy. 6 ) Only a few reports have angiography findings, indicating an overlying thrombus trapped in the CaW, and the thrombus disappeared under anticoagulation therapy Several reports have advocated that a thrombus might respond best to anticoagulation therapy 1 , 2 , 7 ) because blood stagnation may lead to thrombus formation distal to the CaW, followed by artery-to-artery embolism; this mechanism of thrombus formation could be similar to the mechanisms of thrombus formation in the left atrial appendage. We confirmed that antiplatelet therapy did not play a role in preventing either thrombus formation or stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%
“… 5 ) A cohort study also demonstrated that among seven (29%) patients with symptomatic CaWs exhibiting a recurrent ischemic stroke, three were already taking antiplatelet monotherapy and two were using dual antiplatelet therapy. 6 ) Only a few reports have angiography findings, indicating an overlying thrombus trapped in the CaW, and the thrombus disappeared under anticoagulation therapy Several reports have advocated that a thrombus might respond best to anticoagulation therapy 1 , 2 , 7 ) because blood stagnation may lead to thrombus formation distal to the CaW, followed by artery-to-artery embolism; this mechanism of thrombus formation could be similar to the mechanisms of thrombus formation in the left atrial appendage. We confirmed that antiplatelet therapy did not play a role in preventing either thrombus formation or stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%